Examining farmers' perceptions of soil fertility and its use in field practices in Northern Ghana - Yageta, Yoshie; Awuni, Joseph Agebase; Avornyo, Vincent Kodjo; Koide, Junji; Muranaka, Satoru; Nakamura, Satoshi (Geoderma Regional, 2025)
Expanding sustainable soil fertility management is essential for sustainable agricultural production in Sub-Saharan Africa. This case study was conducted to understand local perceptions of soil fertility and strategies farmers use for field management in Northern Ghana. The study objectives were to 1) identify the indicators of farmers' perceptions of soil fertility and 2) assess the impacts of local knowledge of soil fertility on field management, particularly crop selection, in Northern Ghana. Soil sampling for physicochemical analysis and interviews with farmers regarding their perceptions of soil fertility, cultivated crops, and organic amendments were conducted in 300 farm fields in 60 communities. Soils perceived as fertile by farmers had significantly higher values of pH (H2O), pH (KCl), electrical conductivity, total nitrogen, total carbon, Ca, K, Mg, and cation exchange capacity, followed by normal, less fertile, and infertile soils. A comparison of the crops cultivated in 2019 and 2020 at each farm revealed that cash crops (groundnuts, soybeans, and yams) were not cultivated in soils perceived as infertile by farmers. The use of organic amendments was relatively low; however, they were often applied to fields perceived as infertile to improve fertility. Our findings can be useful for recommending suitable crop allocation for specific local conditions.